Autofluorescence Imaging and Methylene Blue‐Mediated Photodynamic Therapy for Early Detection and Management of Subclinical Actinic Cheilitis - Juliana Cristina Oliverio de Araújo; Og Fray Junior; Hermano Camelo Paiva; Alyne Simões Gonçalves; Martha Simões Ribeiro (Journal of Biophotonics, 2026)
ABSTRACT Objectives Optical autofluorescence imaging is a noninvasive adjunct for detecting potentially malignant oral disorders, such as actinic cheilitis (AC). This study evaluated its use for early detection and for monitoring tissue response following methylene blue‐mediated photodynamic therapy (MB‐PDT). Methods Lip autofluorescence was assessed using a handheld device (405 ± 20 nm). Areas with altered fluorescence underwent biopsy for confirmation. Patients with AC received five MB‐PDT sessions (660 nm, 100 mW, 120 s/point) after topical 1% MB. Grayscale intensity was quantified before treatment and at 30 days. Results Of 25 screened individuals, 19 had confirmed AC, and 17 completed follow‐up. Lesions showed higher fluorescence intensity than healthy tissue. After MB‐PDT, mean intensity and variability significantly decreased, indicating tissue response. Smokers showed a smaller reduction. Conclusion Autofluorescence imaging enables early detection and noninvasive monitoring of AC. Combined with MB‐PDT, it represents a practical strategy for managing high‐risk patients and supporting early intervention.